Experimental Study on Temperature Change and Crack Expansion of High Temperature Granite under Different Cooling Shock Treatments - Yan-Jun Shen; Xin Hou; Jiang-Qiang Yuan; Chun-Hu Zhao (Energies, 2019)
It is valuable to observe the influence of different cooling methods on the exploitation of geothermal energy and breaking hard rocks in deep geo-engineering. In this work, the effects of different cooling shock treatments on high temperature granite are discussed. First, perforated 100-mm-side cubic biotite adamellite samples were heated to four targeted temperatures (150 °C, 350 °C, 550 °C, and 750 °C). Then, anti-freeze solutions were compounded to produce the different cooling shock effects (20 °C, 0 °C, and −30 °C) by adjusting the calcium chloride solution concentration, and these anti-freeze solutions were injected rapidly into the holes to reflect the rapid cooling shock of high-temperature granite. Finally, the temperature variations and crack expansions of high-temperature granite under different cooling shock treatments were analyzed and the cooling shock cracking mechanism is discussed briefly. The main results can be summarized as: (1) The high temperature granite exposed to the cooling shock exhibited a "rapid cooling + rapid heating" change during the first 5 min. Due to the cooling shock, the total temperature was significantly lower than the natural cooling until 120 min later. (2) Below 350 °C, the macrocracking effect was not significant, and the sample reflected a certain range of uniform microcracks around the injection hole, while the macrocracks tended to be obvious above 550 °C. Moreover, as the refrigerant temperature decreased, the local distribution characteristics of the macrocracking became more obvious. (3) Based on the analysis of the dynamic heat balance, the undulation and width of the cracks around the heat balance zone were stable, but the numbers and widths of cracks near the hole wall and the side of the sample were visibly increased. This study extends our understanding of the influence of cooling shock on granite cracking.